THE HISTORY OF FORMATION AND THE PRESENT SOCIAL ROLE COMMUNITY COLLEGES USA - Bratko, Mariia (Educological discourse, 2018)
This article represents the results of the scientific research of the community colleges in USA. The author traces the development of community colleges in America from their earliest days through modern times, describing the social, political, religious, and economic factors that influenced their development. The community college evolved from at least seven sources of educational innovation: community boosterism and the rise of the research university (1880s and 1890s.); the advent of universal secondary education, the professionalization of teacher education, and the vocational education movement (from the educational reforms of the Progressive Era (1900–1916); open access to higher education, and the rise of adult and continuing education and community services (were primarily post–World War II phenomena). The community college is largely a phenomenon of twentieth-century American higher education. The label applies to an array of institutions that offer six-month vocational diplomas; one- and two-year vocational, technical, and pre-professional certificates; and two-year programs of general and liberal education leading to an associate degree. Two-year colleges may be public, private, proprietary, or special purpose, although public institutions represent the majority of community colleges in the twentieth-first century. Community colleges in the United States have a considerable popularity, which is growing every year. Community colleges serve the region where were placed, usually a city and district. College students often study in various forms of education (day, evening, distance form) and have the opportunity to work during the day. A special interest of educational manager of Ukrainian colleges is paid on issues concerning governance, financing, access into higher education and cooperation with employers at community colleges.